Influence of Friction Angles on Earth Pressures in Dry Granular Flow Dynamics and Soil Mechanics (The Nepali Mathematical Sciences Report, 2022)
The earth pressure coefficient (K) determines the nature of (tendency of) deformation of the granular mass during flow or deposition. When flow velocity is increasing, K takes its active state Kact and the flow is divergent. When the flow velocity is decreasing, K takes its passive state Kpas and the flow is convergent. The mathematical relations presented here and their 2-D and 3-D plots highlight that the passive and active earth coefficients strongly depend on the internal angle (δ) and basal angle (ϕ) of frictions. The mathematical relation for dry granular mass flow is extended to find these coefficients in soil mechanics. Results further show that active earth pressure drops as the internal angle of friction increases, but passive earth pressure rises. The earth's pressure is at rest if the wall is in its natural position